Comments on the review by Kathrin Tiewa - Amidu, Assibi A. (AAeO - Afrikanistik-Aegyptologie-Online, 2010)
The review of the book Matrix nominal Phrases in Kiswahili Bantu (2009), Rüdiger Köppe Verlag, in Afrikanistik online is lucid and welcome. We appreciate it very much. There are, however, a few inexactitudes that need to be corrected.